Agricultural Adaptation to Climate Change in Africa 2018
DOI: 10.4324/9781315149776-6
|View full text |Cite
|
Sign up to set email alerts
|

Climate, shocks, weather and maize intensification decisions in rural Kenya*

Abstract: We explore how climate, climate risk and weather affect maize intensification among smallholders in Kenya. We find that each plays an important role in maize intensification choice. The economic implications of this choice are also analyzed. We find that the share of maize area planted to hybrid seeds contributes positively to expected crop income, without increasing exposure to income variability or downside risk. The promotion of maize hybrids is potentially a valuable adaptation strategy to support the well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
2
3
1
Order By: Relevance
“…This suggests that adopting at least two coping strategies improves the welfare level of adopters compared to non-adopters. This finding agrees with Alpizar (2007) and Martina et al . (2016), who found comparatively high per capita consumption among households that adopted coping strategies against livelihood shocks in El Salvador and Kenya, respectively.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that adopting at least two coping strategies improves the welfare level of adopters compared to non-adopters. This finding agrees with Alpizar (2007) and Martina et al . (2016), who found comparatively high per capita consumption among households that adopted coping strategies against livelihood shocks in El Salvador and Kenya, respectively.…”
Section: Resultssupporting
confidence: 93%
“…This suggests that adopting at least two coping strategies improves the welfare level of adopters compared to non-adopters. This finding agrees with Alpizar (2007) and Martina et al (2016), who found comparatively high per capita consumption among households that adopted coping strategies against livelihood shocks in El Salvador and Kenya, respectively. The potential outcome mean value of Gh₵6,852.17 implies that if all farmers adopt at least two coping strategies, they would have an average consumption expenditure of Gh₵6,852.17, ceteris paribus.…”
Section: Types Of Coping Strategies Adopted By Farm Households and In...supporting
confidence: 91%
“…While both intensification and natural diversity can lead to differences in texture and colour, the core concepts used by farmers for their evaluation of soil in both locations was the same. Given national interest in supporting intensification of these soils, understanding the underlying epistemological framings for management decisions by farmers are vital (Bozzola, Smale and Falco, 2016;Verkaart et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Smallholder farmers are faced with multiple climate change shocks, including floods, erratic rains, dry spells, drought, among others [ 50 , 51 ]. The climate change shocks significantly affect agricultural productivity, including total crop failure and livestock losses.…”
Section: Introductionmentioning
confidence: 99%